OBSTETRICAL REFERRALS BY TRADITIONAL BIRTH ATTENDANTS - Mustafa, Rozina; Hashmi, Haleema; Mustafa, Rubina (Journal of Ayub Medical College Abbottabad, 2012)
Background: In Pakistan 90% of births are conducted by TBA's. In most cases, TBA's are unable to diagnose the complications and are often unable to take decisions on timely referral. The objective of this study was to determine the prevalence, nature and outcome of life threatening obstetrical conditions in referrals by Traditional Birth Attendants (TBAs). Methods: This Observational, Descriptive study was conducted from January to December 2007, in the obstetrical unit of Fatima Hospital, Baqai Medical University, a tertiary care community based hospital. The study included patients referred by TBA's who developed life threatening obstetric conditions (LTOCs). Results: Total 64 patients were referred by TBA's. The prevalence was 7.8%. Out of them, 53 (82.8%) patients admitted with life threatening obstetric conditions. The near-miss morbidities and mortalities were 45 (84.9%) and 8 (15%) respectively. Maternal mortality to Near-miss morbidity ratio was 1:6. Obstructed labour caused near-miss morbidity in 32 (60.3%) patients with no mortality. Postpartum haemorrhage as life threatening condition developed in 16 (30.1%) patients with 10 (18.8%) near-miss morbidities and 6 (11.3%) mortalities. Puerperal sepsis accounted for 1 (1.88%) near-miss morbidity and 2 (3.76%) mortalities. The mortality index for puerperal sepsis is (66.6%) almost double of postpartum haemorrhage (37.5%). Conclusion: Mortality to near miss morbidity ratio is high. Misidentification and late referrals of complicated cases by TBA's were responsible for near-miss morbidities and mortalities. Keywords: Traditional Birth Attendants, Life threatening obstetric conditions, Maternal mortality